HAMBATAN ORANG DENGAN HIV DALAM MENGAKSES PEKERJAAN: SISTEMATIC REVIEW: Hambatan Orang Dengan HIV Dalam Mengakses Pekerjaan: A Sistematic Review - Ossi Dwi Prasetio; Manggar Purwacaraka; Shulhan Arief Hidayat; Rio Ady Erwansyah (Jurnal Keperawatan Terapan, 2025)
Abstract: Background: People living with HIV/AIDS (PLHIV) often experience health, social, and economic challenges, as well as daily challenges in self-care and meeting their social, economic, and psychological needs. People living with HIV/AIDS (PLHIV) often face barriers to employment due to stigma and discrimination, as well as health factors such as fatigue. Objective: This study aims to identify barriers facing people living with HIV/AIDS (PLHIV) in accessing employment. Methods: Systematic reviews were identified in four electronic databases published between 2019 and 2024. The quality of the reviewed studies was assessed using the Critical Appraisal Skills Program. Data were extracted by the researchers and analyzed using thematic analysis. Results: This review included twelve eligible studies. The review found that stigma, support, environment, and empowerment were both solutions and barriers to employment for people living with HIV/AIDS (PLHIV). Providing support, eliminating stigma, providing a positive environment, and empowering people living with HIV/AIDS (PLHIV) can improve their quality of life and meet their primary needs. Conclusion: Barriers to accessing employment experienced by PLHIV can be controlled through environmental empowerment by forming a support group.